Gender Discrimination in Iran’s Capital Punishment System - Alasti, Sanaz (Women & criminal justice, 2025)
This study explores gender discrimination and sex bias in Iran’s capital punishment system, reviewing the story of women on death row in Islamic and totalitarian criminal justice systems. It reaches back to the classical Islam to trace how and why sharia law discriminates against women. It discuses original findings and is the first research to focus on execution of women in Iran. A small but emerging body of literature focuses on capital punishment in Iran but does not examine gender in detail. The role of Iran’s Islamic criminal justice system for women, particularly in the context of changes and gender bias after the Islamic revolution, is examined. There is substantial literature on mariticide (women killing their husbands) and filicide (women killing their children), but insufficient literature on gender discrimination in Iran’s capital punishment system. This study provides a profile of 155 women and examines how decision-making in an Islamic criminal justice system has influenced these cases.